Analysis of The Leading Sector for Regional Development: A Case Study of Batam, Bintan, and Karimun (BBK), Riau Islands Province, Indonesia - Wahyuni, Sri; Siregar, Hermanto; Rustiadi, Ernan; Pravitasari, Andrea Emma (BHUMI: Jurnal Agraria dan Pertanahan, 2024)
Abstract: Spatial planning in Batam, Bintan, and Karimun (BBK) areas is prioritized because it has an important impact on the national economy. This research aims to identify the potential leading sectors in the BBK areas as a reference in regional development. This study uses time series data on Gross Regional Domestic Product (GRDP) based on constant prices in the BBK areas from 2011 to 2021. The analytical tools used in this research are Location Quotient to identify basic and non-basic sectors, Shift Share Analysis to determine changes and shifts in sectors, and Klassen Typology to determine the classification of sector in each region. The three analytical tools combined results demonstrate that economic growth in Batam is supported by the processing sector. A growing sector in Bintan is related to the tourism. Economic potential in Karimun dominated by the agricultural, forestry, and marine sectors. Tanjungpinang’s economic potential is dominated by the service sector, which supports the city’s role as the capital of the Riau Islands Province. However, the fisheries sector has not developed optimally. As an archipelago, regional development policies in the BBK areas should develop other sectors to optimize the maritime economic potential. Keywords: Klassen Typology, Location Quotient, Leading Sectors, National Strategic Areas, Shift Share Analysis